Organizational commitment: an ever-shifting concept forever changed by COVID-19. Issue 2 (15th March 2023) - Chauhan, Rahul S.; Howe, David C.; Nachmias, Stefanos
ABSTRACT: Evolving from the concept of organizational loyalty, organizational commitment (OC) is a construct that we propose is both dated and lacking in the literature. Our paper aims to address critical gaps in OC literature as it pertains to human resource development for the modern work setting by highlighting three salient elements that have a significant impact on OC on an international scale. We posit that technology, dynamic markets, and globalization are crucial aspects of OC that are largely omitted by the literature in this domain and should be further examined to enhance our understanding of OC as it pertains to human resources development. We also highlight the profound influence that the COVID-19 pandemic has had on OC from a human resources development perspective across the globe. Implications for practitioners and researchers are discussed.